Grenada : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2006)
Grenada quickly recovered from the devastating effects of Hurricane Ivan. Executive Directors welcomed the economic reform program aimed to promote economic growth, restore fiscal and debt sustainability, reduce vulnerabilities, and alleviate poverty. They emphasized the need to strengthen the financial regulatory framework and accelerate structural reforms. They agreed that steadfast policy implementation can reduce debt and fiscal sustainability. They commended that the new strategy will help to address its economic and social challenges, and recommended for an arrangement under the Poverty Reduction and Growth Facility.